2019
DOI: 10.1002/prot.25678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PI(4,5)P2 concentration on the F‐BAR domain membrane binding as revealed by coarse‐grained simulations

Abstract: Bin/Amphyphysin/Rvs (BAR) domain proteins form a key link between membrane remodeling and cytoskeleton dynamics. They are dimers that bind to membranes via electrostatic interactions with different preferences toward negatively charged lipids. In the present article, we examine the interactions of the F‐BAR domain of nervous wreck (Nwk) with phosphatidylinositol 4,5‐bisphosphate (PI(4,5)P2)‐containing membranes using coarse‐grained molecular dynamics. We demonstrated PI(4,5)P2 concentration effects, identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[109] MD studies further demonstrated the importance of positive residues on the BAR domains and lipid composition as parameters in curvature-dependent protein recruitment. [110,111] As such, MD has positioned itself as a significant contributor in determining the role of curvature during mechanical deformation associated with cellular processes and signaling. Yet, atomistic and coarsegrain MD studies rely on force fields that represent the basic physical properties of proteins and lipids as the membrane bends.…”
Section: Studying Curvature-dependent Processes In Silicomentioning
confidence: 99%
“…[109] MD studies further demonstrated the importance of positive residues on the BAR domains and lipid composition as parameters in curvature-dependent protein recruitment. [110,111] As such, MD has positioned itself as a significant contributor in determining the role of curvature during mechanical deformation associated with cellular processes and signaling. Yet, atomistic and coarsegrain MD studies rely on force fields that represent the basic physical properties of proteins and lipids as the membrane bends.…”
Section: Studying Curvature-dependent Processes In Silicomentioning
confidence: 99%